Expression of the IL-2R in Human Podocytes and the Effect of Activation on Autophagy and Apoptosis. (6th October 2021) - Stewart, Tyrus; Zea, Arnold; Aviles, Diego
Abstract: Background: Interleukin 2 (IL-2) treatment is associated with proteinuria. Materials and Methods: A conditionally immortalized human podocyte cell line was used to investigate expression of the podocyte specific marker podocin, IL-2R alpha (IL-2Rα), apoptosis marker Bax, and autophagy markers LC3I AND LC3II, determined by quantitative immunoblotting, following 24, 48, and 72 hours of IL-2 stimulation, comparing them to unstimulated cells. Results: Podocin was expressed at all time points. IL-2Rα expression was increased after 24 and 72 hrs ( p =  0.0014, p =  0.0139) and decreased after 48 hours ( p =  0.0445). Bax, LC3I, and LC3II were increased after 24 hrs ( p =  0.0094, p =  0.0016, p =  0.0004) and 48 hrs ( p =  0.0072, p =  0.0024, p =  0.0087). Conclusion: Human podocytes express the IL-2R and activation results in increased autophagy and apoptosis.